Implementasi Algoritme SPECK Pada Proses Pengiriman File Multimedia Melalui Jaringan Internet - David Christanto; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Audio recording is one of the multimedia files that are often encountered today. One example is the sound recording that can be used as evidence in the trial of the law. The proof of sound recording is supported by UU No 11 Tahun 2008 Pasal 5 ayat 1 regarding information and electronic transactions that stated : "Electronic information and / or electronic documents and / or prints are legal evidence". Therefore, sound recording is very important to be kept secret from an unauthorized party. This study focuses on the aspect of confidentiality. This research implements SPECK algorithm to encrypt audio recordings. DHKE is also implemented as a public key exchange algorithm. Execution time encryption and decryption is performed by using various files extension and the duration of different audio recordings. The time of encryption and decryption of each file extension is slightly different. The execution time difference of encryption and decryption is less than 23 seconds. The results show that the file extension does not affect the execution time. The execution time is affected by the size of the file, whichs mean the bigger the size of the file, the longer the execution time.